Les récits littéraires d’apprentissage : un corpus pour la didactique du FLE - Berthu-Courtivron , Marie-Françoise; Bourvon , Marie-Françoise; Richard , Élisabeth (Neofilolog, 2022)
If language biography „is based on the individual’s ability to recount the constituent elements of his or her experience in the linguistic and cultural domains” (Molinié, 2006: 1), we argue that this ability to recount is exemplary among allophone authors who have become writers in French and that their language (auto)biographies constitute a corpus that should be promoted for the teaching of literature in FLE. Each author is in fact an autobiographer who, text after text, continues to „reappropriate his or her own language history as it has been constituted over time” (Perregaux, 2002: 83). The works, written by learners who have already become authors, all recount the hazards of learning French, whether in an institutional or informal context, and the difficulty of the in-between languages and cultures (Alcoba, Alexakis, Cheng, Djavann, Huston, Kang, Svit, Wei-Wei...). These works are all marked by doubling and interlocution, and even when French has been known for a long time, by the omnipresence of reflection on language. For the learner who has become a writer, language is no longer just a tool but becomes a theme. The problem of writing in French thus continues to underlie the works explicitly: whether it is a question of the authors asserting their linguistic expertise in creation or showing the way to otherness.